PENGEMBANGAN SIKAP RELIGIUS PADA ANGGOTA RESIMEN MAHASISWA (MENWA) MAHAPURA IAIN PONTIANAK - Sukino Sukino; Agus Handini; Agnia Wara ‎ (Ta'allum: Jurnal Pendidikan Islam, 2021)
This study discusses efforts to develop religious attitudes among students which are always important to be carried out by institutions through Student activity units independently so that their potential as leaders is honed based on moderate Islamic religious values. The purpose of this study was to obtain information about: 1) program activities designed by the commander and staff in shaping the religious character of the members of the MENWA. 2) challenges faced in implementing program activities in shaping the religious character of members of the Mahapura student regiment. The research approach was qualitative, the data source of this study consisted of primary data sources of menwa and secondary leaders (Menwa members), Mahapura IAIN Pontianak. This study found a program of religious development activities namely, Yasisnan and Tahlilan, Khataman al-Quran, and social care: Menwa Sharing through fundraising, the two challenges faced in developing religious attitudes are forgiving excessive self-weakness, lack of interest in religion, and lack of interest in religion. Sense of responsibility due to feeling tired after participating in activities on campus. This finding becomes a new model for the development of religious attitudes among intra-campus organizations in preparing a generation that is physically strong and has a strong faith